Pyramiding BPH genes in rice maintains resistance against the brown planthopper under climate change - Wang, Chih-Lu; Luo, Pei-Qi; Hu, Fang-Yu; Li, Yi; Sung, Chang-Lin; Kuang, Yun-Hung; Lin, Shau-Ching; Yang, Zhi-Wei; Li, Charng-Pei; Huang, Shou-Horng; Hechanova, Sherry Lou; Jena, Kshirod K.; et al. (Wiley, 2024)
Nilaparvata lugens (brown planthopper; BPH) is a significant rice pest in Asia, causing substantial yield losses. Pyramiding BPH resistance genes with diverse resistance traits into rice cultivars is an effective strategy for pest management. However, the response of pyramiding combinations to environmental changes remains unclear. To address this knowledge gap, we investigated three pyramiding rice lines (BPH2 + 32, BPH9 + 32, and BPH18 + 32) in the context of varying climate change conditions, ensuring sufficient N. lugens–rice interactions. Thus, we set three environmental conditions [30/25 °C (day/night) with 500 ppm CO2 concentration, 32/27 °C (day/night) with 600 ppm CO2 concentration, and 35/30 °C (day/night) with 1000 ppm CO2 concentration].RESULTSAll three pyramiding rice lines maintained the insect resistant ability under the three environmental settings. In particular, the BPH18 + 32 rice line exhibited stronger antibiotic and antixenosis effects against N. lugens. In addition, BPH18 + 32 rice line had better shoot resilience under N. lugens infestation, whereas the performance of the other two selected pyramiding rice lines varied. Thus, although BPH2, BPH9, and BPH18 represent three alleles at the same locus, their resistance levels against N. lugens may vary under distinct climate change scenarios, as evidenced by the performance of N. lugens on the three pyramiding rice lines.CONCLUSIONOur findings indicate that all three tested pyramiding rice lines maintained their insect resistance in the face of diverse climate change scenarios. However, these lines exhibited varied repellent responses and resilience capacities in response to climate change. Thus, the combination of pyramiding genes needs to be considered for future breeding programs. © 2023 Society of Chemical Industry.